The Dualism of The Existence of 'Sopi' in Maluku Between a Sacred Traditional Symbol and a Criminogenic Symbol - Raihana Uar (Activa Yuris: Jurnal Hukum, 2026)
Corruption is a serious and systemic problem that has wide-ranging impacts on governance, national development, and public trust in state institutions. Efforts to combat corruption cannot rely solely on law enforcement but must also be supported by sustainable preventive strategies through education. Anti-corruption education plays a strategic role in shaping the character of younger generations by promoting values such as integrity, honesty, responsibility, and discipline. Through a structured educational process, individuals are equipped with knowledge, moral awareness, and skills to recognize, prevent, and resist corrupt practices. This study aims to analyze the urgency of anti-corruption education as an instrument for fostering an anti-corruption culture in Indonesia. The research employs a literature review method by examining legal regulations, national policies, reports from international organizations, and relevant previous studies. The findings indicate that anti-corruption education significantly contributes to enhancing legal and moral awareness, strengthening ethical values, and promoting transparent and accountable governance. Therefore, anti-corruption education constitutes a crucial long-term investment in achieving a just, prosperous, and corruption-free society.